The Impact of Leadership, Work Environment, and Motivation on Employee Performance: Evidence from Bank Rakyat Indonesia Jayapura Branch - Patanduk, Subiar Abraham; Kambuaya, Balthasar; Tuhumena, Ruben (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study aims to analyze the impact of leadership, work environment, and motivation on employee performance at Bank Rakyat Indonesia (BRI) Jayapura Branch. A descriptive quantitative approach was employed with a total population of 110 employees, all of whom were included as the research sample (census sampling). Data were collected through questionnaires and observations, and analyzed using multiple linear regression. The findings indicate that leadership, work environment, and motivation each have a significant partial effect on employee performance. Simultaneously, these three variables contribute 56.8% to employee performance, with work motivation emerging as the dominant factor. The results highlight the importance of implementing effective leadership, improving the work environment, and strengthening employee motivation as key strategies for enhancing organizational performance.